2017
DOI: 10.1017/pao.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal helminths of stray dogs from Tunisia with special reference to zoonotic infections

Abstract: Sixteen intestinal helminth species were recovered from 271 necropsied stray dogs during a survey undertaken in Raoued and Soukra, two northeastern rural regions of Tunisia. Recorded parasites included trematodes (Brachylaemus sp., Phagicola italica, Heterophyes heterophyes), cestodes (Echinococcus granulosus, Dipylidium caninum, Diplopylidium noelleri, Mesocestoides lineatus, Mesocestoides litteratus, Taenia hydatigena, Taenia pisiformis, Taenia multiceps), nematodes (Toxocara canis, Ancylostoma caninum, Unci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
2
8
1
Order By: Relevance
“…Few studies in Nigeria have demonstrated the presence of ova of intestinal helminths in the stools of dogs [5][6][7], [9], [20][21]. Some of the helminth ova observed in this study were reported in other studies conducted in other parts of the world [22][23][24][25][26][27][28][29][30][31][32] . The report of these various studies showed that species of Ancylostoma, Toxocara and Dipylidium are the most widely distributed gastrointestinal helminth parasites of stray dogs globally, while S. stercoralis seems to be the least.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Few studies in Nigeria have demonstrated the presence of ova of intestinal helminths in the stools of dogs [5][6][7], [9], [20][21]. Some of the helminth ova observed in this study were reported in other studies conducted in other parts of the world [22][23][24][25][26][27][28][29][30][31][32] . The report of these various studies showed that species of Ancylostoma, Toxocara and Dipylidium are the most widely distributed gastrointestinal helminth parasites of stray dogs globally, while S. stercoralis seems to be the least.…”
Section: Discussionsupporting
confidence: 65%
“…The report of these various studies showed that species of Ancylostoma, Toxocara and Dipylidium are the most widely distributed gastrointestinal helminth parasites of stray dogs globally, while S. stercoralis seems to be the least. However, other studies have identified some other species of gastrointestinal helminths like Ascaris species, Trichuris trichiura [3], Taenia species, Mesocestoides species [33], Toxascaris leonine [28], Uncinaria stenocephala, Trichinella species [34], and Heterophyes heterophyes [32]. It was observed that the distribution and prevalence of these parasites differ slightly from one study area to another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, necropsy remains as the gold standard technique for screening helminth fauna in hunted animals while coproscopy represents a supplementary test utilized to complement observed results. Macracanthorhynchus hirudinaceus encountered in the present investigation at high prevalence (61.7% ± 0.03) has been previously reported from necropsied wild canids and stray dogs in Tunisia (Lahmar et al ., 2009 a , 2017) as well as from swine in other countries (Eslami and Farsad-Hamdi, 1992; Solaymani-Mohammadi et al ., 2003; Foata et al ., 2005; Senlik et al ., 2011; Mansouri et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to Lahmar et al (2017), in some countries rural stray dogs are mainly transmitting the tapeworm in the environment. Taenia hydatigena was also detected in dogs in Poland and Ukraine (Okulewicz et al 1994; Komyushin et al 2013; Karamon et al 2016).…”
Section: Introductionmentioning
confidence: 99%